Optical measures of cerebral arterial stiffness are associated with white matter signal abnormalities and cognitive performance in normal aging - Tan, Chin Hong (2020)
Decline in fluid abilities in normal aging is associated with increased white matter lesions, measured on T1-weighted images as white matter signal abnormalities (WMSAs). WMSAs are particularly evident in hypertensive older adults, suggesting vascular involvement. However, because hypertension is assessed systemically, the specific role of cerebral arterial stiffening in WMSAs has yet to be demonstrated. In 93 cognitively normal adults (aged 18-87 years), we used a novel method to measure cerebral arterial elasticity (pulse relaxation function [PReFx]) with diffuse optical tomography (pulse-DOT) and investigated its association with WMSAs, age, and cognition. PReFx was associated with WMSAs, with older adults with low PReFx showing the greatest WMSA burden. PReFx in brain regions perfused by the middle cerebral artery showed the largest associations with WMSAs and partially mediated the relationship between age and WMSAs. Finally, WMSAs partially mediated the relationship between PReFx and fluid but not crystallized abilities scores. Taken together, these findings suggest that loss of cerebral arterial elasticity is associated with cerebral white matter lesions and age-related cognitive decline.